Pengaruh Penggunaan Metode Penugasan terhadap Hasil Belajar Matematika pada Operasi Bilangan Kompleks Siswa di Kelas XI SMA Anugera Gloria Terpadu Wamena Tahun Ajaran 2023/2024 - Yeheskiel Lolopayung; Andinus Yanengga; Barthon Wenda; Christine M Rumpaisum; Arnima Abung (PT PUSTAKA CENDEKIA GROUP, 2024)
The aim of this research is to see the effect of using the Assignment Method on Mathematics Learning Outcomes in Complex Number Operations for Class This type of research is quantitative, with a research design of all students in class XI IPS SMA Anugerah Gloria Terpadu Wamena totaling 28 students with the number of class student. Data collection techniques in this research used questionnaire methods, test methods, observation and documentation methods. To test quantitative data analysis with hypothesis testing using SPSS 21, the following results were obtained: test results using SPSS version 21, the t test obtained a value of 3.652 with a decision making if the calculated T value > T table then Ha was accepted and Ho was rejected, with The T table value for 28 respondents is 2.059, meaning 3.652 > 2.059, so Ha in this study is accepted and H0 is rejected. It can be concluded that there is an influence of the use of the Assignment Method on Mathematics Learning Outcomes in Complex Number Operations for Class.